Cathepsin G Induces Cell Aggregation of Human Breast Cancer MCF-7 Cells via a 2-Step Mechanism: Catalytic Site-Independent Binding to the Cell Surface and Enzymatic Activity-Dependent Induction of the Cell Aggregation - Riyo Morimoto-Kamata; Sei-ichiro Mizoguchi; Takeo Ichisugi; Satoru Yui (Hindawi Limited, 2012)
Neutrophils often invade various tumor tissues and affect tumor progression and metastasis. Cathepsin G (CG) is a serine protease secreted from activated neutrophils. Previously, we have shown that CG induces the formation of E-cadherin-mediated multicellular spheroids of human breast cancer MCF-7 cells; however, the molecular mechanisms involved in this process are unknown. In this study, we investigated whether CG required its enzymatic activity to induce MCF-7 cell aggregation. The cell aggregation-inducing activity of CG was inhibited by pretreatment of CG with the serine protease inhibitors chymostatin and phenylmethylsulfonyl fluoride. In addition, an enzymatically inactive S195G (chymotrypsinogen numbering) CG did not induce cell aggregation. Furthermore, CG specifically bound to the cell surface of MCF-7 cells via a catalytic site-independent mechanism because the binding was not affected by pretreatment of CG with serine protease inhibitors, and cell surface binding was also detected with S195G CG. Therefore, we propose that the CG-induced aggregation of MCF-7 cells occurs via a 2-step process, in which CG binds to the cell surface, independently of its catalytic site, and then induces cell aggregation, which is dependent on its enzymatic activity.